A Qualitative Model Demonstrating the Adaptation of Amphibians to Semi-Arid and Arid Habitats: Comparing the Green Toad Bufotes sitibundus (Pallas, 1771) and Pelophylax bedriagae (Camerano, 1882) - Gad Degani (Animals)
In this brief article, the green toad (Bufotes sitibundus) and the Levant water frog (Pelophylax bedriagae) were compared to better understand the adaptations needed by amphibians, specifically the green toad, to survive in arid regions and to inhabit a wide range of habitats. The information mainly comes from data gathered in Israel, a nation experiencing a shift from Mediterranean to desert ecosystems where both amphibian species can be found. Using these data, a qualitative model is put forward that showcases the differences between these two amphibians and illustrates how the green toad has adapted to arid environments. For instance, green toads travel to breeding and spawning sites during the rainy season. During this journey, they often have to cross roads, which puts them at risk of being hit by vehicles. The main distinction between the green toad and the water frog is that the green toad moves from land environments to water, while the water frog stays in its aquatic habitat for its entire life cycle.